Phonons and magnons in stripe-ordered nickelates. A Raman scattering study - Gnezdilov, V.; Kurnosov, V.; Pashkevich, Yu.; Lemmens, P.; Tranquada, J.; Choi, K.-Y.; Gьntherodt, G.; Nakajima, K.; Yeremenko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Electronic correlation effects in La2–xSrxNiO4 (x = 1/3 and 0.225) lead to spontaneous phase separation into microscopic spin/charge stripes with commensurate and incommensurate order, respectively. Raman scattering experiments on such single crystalline materials show a rich phenomenology of phonon and magnon anomalies due to the new, self-organized periodicities. These effects are observable as function of temperature but can also be induced by cooling in a seemingly small magnetic field leading to a reorganization of stripe structure.